Dairy Products and Prevention of Type 2 Diabetes: Implications for Research and Practice - Kalergis, Maria; Leung Yinko, Sylvie S.; Nedelcu, Roxana (Frontiers in Endocrinology, 2013)
A growing body of scientific evidence has linked dairy intake to a reduced type 2 diabetes (T2D) risk. Using an evidence-based approach, we reviewed the most recent and strongest evidence on the relationship between dairy intake and the risk of T2D. Evidence indicates that dairy intake is significantly associated with a reduced T2D risk, and likely in a dose-response manner. The association between low-fat dairy and T2D risk reduction appears consistent. A beneficial impact is suggested for regular-fat dairy. The role of specific dairy products needs to be clarified. Potential underlying mechanisms include the role of dairy products in obesity and metabolic syndrome, as well as several dairy components, such as calcium, vitamin D, dairy fat and specifically trans-palmitoleic acid. To conclude, there is strong, consistent and accumulating evidence that dairy intake reduces the risk of T2D. More research is needed to better understand the role of regular-fat and specific dairy products. Well-designed randomized controlled trials and mechanistic studies are needed to support these findings. Efforts to translate this evidence into clinical practice and public health guidance are needed.